2020
DOI: 10.21608/jfds.2020.160389
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of ISO 22000 System in Spaghetti Industry

Abstract: The ISO 22000 Food Safety Management System has been applied to the spaghetti industry, in order to enhance food protection, protect customers, increase customer trust and improve cost efficiency. This experiment was carried out in North Cairo Flour Mills and Bakeries Company, Pasta Factory, Shubra El Khema, Cairo, Egypt, all stages were followed up from the receiving wheat flour extract 72% to spaghetti production and storage. Beginning with the appointment of the food safety team and that the infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…ISO 22000 certification also provides assurance within the global supply chain, allowing products to cross borders and increasing the confidence of customers [11]. To demonstrate that, El-Rouby et al [31] reported the implementation of the ISO 22000 food safety management system in a spaghetti industry that outputted enhanced food protection, increased customer trust, and improved cost efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ISO 22000 certification also provides assurance within the global supply chain, allowing products to cross borders and increasing the confidence of customers [11]. To demonstrate that, El-Rouby et al [31] reported the implementation of the ISO 22000 food safety management system in a spaghetti industry that outputted enhanced food protection, increased customer trust, and improved cost efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can help the food industry to comply with laws, meet food safety requirements for customers, and produce products that are safe for consumers because they have an impact on reducing foodborne diseases. In addition, the implementation of HACCP in the food industry has a good impact on company finances which leads to an increase in company profits, increased sales, and reduced production costs [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%